Childhood Pemphigus Foliaceus with Exclusive Immunoglobulin G Autoantibodies to Desmocollins. Issue 1 (January 2016) - Geller, Shamir; Gat, Andrea; Harel, Avikam; Mashiah, Jacob; Zeeli, Tal; Eming, Rüdiger; Ishii, Norito; Hertl, Michael; Hashimoto, Takashi; Sprecher, Eli
Abstract: Pemphigus refers to a group of potentially fatal blistering skin diseases that are often due to the deleterious effects of autoantibodies directed against desmosomal antigens. Although desmogleins have been mainly implicated as autoantigens in pemphigus, a steadily growing body of evidence suggests that other desmosomal proteins may be causally involved as well. Antibodies directed against desmocollin‐3 have been shown to play a direct role in the pathogenesis of several types of pemphigus. Here we describe the case of a child with localized pemphigus foliaceus and immunoglobulin G (IgG) reactivity exclusively directed to desmocollins. The present report suggests that autoantibodies against nondesmoglein antigens may play a role in the pathogenesis of superficial pemphigus, in addition to pemphigus vulgaris, paraneoplastic pemphigus, and IgA pemphigus.